Manifesto for a new journal - Robin Bunton; JCPH Editorial Collective (Journal of Critical Public Health)
Academic publishing is in a parlous state. In the context of the rise of populist politics, the use of misinformation and the generation of mistrust in scientific expertise, the need for informed and reasoned counter-critique has never been greater. Yet, opportunities for undertaking and publishing such critique are diminishing with the increased commercialization of academic publishing and research (Speed & Mannion 2017). There is thus a very real need to hold onto the historical gains made in establishing spaces for critical engagement.  In this editorial, we reflect on this context and set out a manifesto for maintaining a space for critique in this new journal.